Investigation of Protective Factors against Career Stress of Senior University Students Using Mixed Pattern Method - Kara, Ahmet (ISRES Publishing, 2023)
Career stress includes negative career experiences such as encountering career barriers, career indecision. This research aims to analyse and evaluate the protective factors against the career stress of senior university students with mixed-method research. For this purpose, an embedded design was used. A total of 353 individuals [AgeMean =23.55, AgeSd = 3.87], determined by sampling method, participated in the research. Data, Dispositional Hope Scale, Career Adaptabilities Scale, Career Decision-Making Self-Efficacy Scale, Career Stress Inventory, and Online Questionnaire were used. Structural equation modeling was used in quantitative data analysis. The content analysis technique was used for qualitative data analysis. As a result of the structural equation modeling analysis in quantitative findings, a protective structural model was obtained against the career stresses of senior university students. The participants revealed several ways to cope with career stress in qualitative findings. The study also examines hope, expectations for self-development, orientation towards activities that make senior students feel good, presence of those experiencing similar stress, positive inculcation, and evaluation of the effects of intrinsic/extrinsic motivators.
Keywords: Hope; Career stress; Career adaptability; Career decision-making; Özel Eğitim ve Engelli Eğitimi; Special Education and Disabled Education; 4. Education